Arthritis as a clinical manifestation of antineutrophil cytoplasmic antibody-associated systemic vasculitis: diagnostic difficulties - T. V. Beketova; V. S. Sygyrta; N. V. Chichasova; N. F. Frolova; E. S. Stolyarevich; O. N. Kotenko (Современная ревматология)
The clinical picture of the symptomatic phase of antineutrophil cytoplasmic antibody-associated systemic vasculitis (ANCA-SV) can vary widely and be accompanied by joint damage, which complicates the early diagnosis of the disease. The paper presents a case of ANCA-SV with acute kidney injury, the manifestations of the symptomatic phase of which were confined to joint damage, myalgia, and Raynaud's syndrome, which led to delayed diagnosis at the stage of renal failure requiring hemodialysis (HD). Urgent adequate induction therapy could preserve kidney function, despite 10-day anuria and 5-week HD.The paper discusses the need for a systematic detailed examination of patients with the onset of a joint inflammatory lesion, especially in those with its systemic manifestations, and the inclusion of serum ANCA tests in the standards of diagnosis in early arthritis.